Desain dan Perancangan Booklet sebagai Instrument dalam Pencegahan dan Penanggulangan Penyakit Obesitas di Sekolah Menengah Pertama Kota Palembang - Sartono, Sartono; Putri, Indah Afifah; Nurmanisa, Chienia; Zelda, Zaneta (Poltekkes Kemenkes Palembang, 2025)
Background: This research was motivated by observational data which showed that students' knowledge of obesity was very low. To respond to this, researchers conducted research aimed at increasing students' knowledge with the help of booklet media. The objectives to be achieved in this research include increasing students' knowledge about obesity. This research was conducted on students in grades 7 and 8 with a total of 27 students. The results of the research using pre-experimental methods showed an increase in students' knowledge after being given booklet media. Methods: This research was carried out as a quantitative research with a pre-experimental type. The pre-experimental method or One Group Pre-Post Test research is a research method that only uses an experimental group without a control/comparison group. With the form of a pretest-post test design, this research aims to see the differences in obese students before and after being given prevention and treatment using booklet media. Results: Based on statistical analysis using the Wilcoxon Signed Rank Test, it was found that the p-value = 0.000 (smaller than 0.05), which shows that there is a significant difference between students' knowledge before and after being given education. Conclusion: Based on the results of statistical analysis, it shows that the use of booklet media has a significant influence in increasing students' knowledge regarding the prevention and management of obesity.